Review of the Diplazontinae (Hymenoptera, Ichneumonidae) of the Kuril islands, with descriptions of two new species - Klopfstein, Seraina (Zootaxa, 2014)
A sample of 346 specimens of Diplazontinae parasitoid wasps from the Kuril islands was studied. Twenty-six species are reported, Tymmophorus gelidus Dasch for the first time for the Eastern Palaearctic. Two new species are described, Diplazon kurilensis sp. n. and Homotropus formosus sp. n. Diplazon urupensis Uchida is removed from synonymy (stat. rev.), and Promethes persulcatus Nakanishi is suggested as a synonym of Promethes bridgmani Fitton. Reasons are discussed for the large proportion of species with a Holarctic or even multi-regional distribution in the sample, which amounts to17 of the species or 65%.